EFFECT OF INDOLE EXTRACTED FROM UROPATHOGENIC E. coli ON SOME CELL LINES IN COMPARABLE WITH STANDARD INDOLE - Abdulazeez. H. Alqaisi,; Mouruj A. Al aubydi, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
Indole mechanism as an interspecies signal particle to adjust various physiological actions, like virulence, antimicrobial and acid resistance. This study was aimed to use partial purified indole extracted from uropathogenic E. coli and study the cytotoxic effect on some cancer cell lines (A375, HepG2, PC3) and comparable with normal cell line (WRL- 68). Serial dilutions of natural and synthetic standard indole were tested (400, 200, 100, 50, 25, 12.5, and 6.25 μg/mL). The results show a low cytotoxic effect for both natural and synthetic indoles in HepG2 and A375 cell lines as well as this degree of cytotoxicity was obviously appeared in normal cell line WRL-68 with no significant differences among them. While, both indoles effect was appeared high cytotoxic effect on PC3 cell line, this increasing has a significant difference with WRL-68.   Thus, it can be suggesting that, this type of indole is not favorable for treatment of some types of cancer, and may has a specific biological activity against exact cancer cells.